1994
DOI: 10.1038/bjc.1994.184
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived growth factor (PDGF) in neoplastic and non-neoplastic cystic lesions of the central nervous system and in the cerebrospinal fluid

Abstract: Summary The aim of this study was to determine the concentration of PDGF in vivo in neoplastic and non-neoplastic brain lesions. Fluid from cystic lesions and cerebrospinal fluid was tested in a radioreceptor assay that detects all described PDGF isoforms. High concentrations of PDGF were found in cyst fluids from several astrocytomas, one metastatic melanoma, one metastatic lung adenocarcinoma and one intracerebral abscess. The PDGF concentrations were several times higher than the levels known to be required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…PDGF, like the neurothrophins, is 1) produced locally and is important for the development, differentiation, proliferation, and survival of neuronal and glial cells (7,10,11,17); 2) coupled to tyrosine kinase receptors that activate complex intracellular signaling pathways (2); and 3) released as part of the compensatory response to central nervous system injury or disease (13,15,16). We now report that PDGF exerts another function that is characteristic of the neurotrophic factors, which is the modulation of neurotransmitter receptors in the central nervous system (29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PDGF, like the neurothrophins, is 1) produced locally and is important for the development, differentiation, proliferation, and survival of neuronal and glial cells (7,10,11,17); 2) coupled to tyrosine kinase receptors that activate complex intracellular signaling pathways (2); and 3) released as part of the compensatory response to central nervous system injury or disease (13,15,16). We now report that PDGF exerts another function that is characteristic of the neurotrophic factors, which is the modulation of neurotransmitter receptors in the central nervous system (29).…”
Section: Discussionmentioning
confidence: 99%
“…Elevations of PDGF levels in the central nervous system have been detected during neurological diseases associated with excitotoxicity and neuronal death such as infections, trauma, and cerebrovascular ischemic disease (13,15,16). Therefore, the inhibitory actions of PDGF on NMDA-R function could also be important in the pathophysiology of these conditions because a decrease in Ca 2ϩ influx through NMDA-Rs should help to restore homeostasis and prevent cell death.…”
Section: Fig 4 Effects Of Pdgf On Nmda-r Function In Xenopus Oocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, plasma proteins constitute a major fraction of gliomatous cyst fluids [20,31]. At least for PDGF in human glioma cysts Nister et al [25] were able to demonstrate by comparison of PDGF and platelet derived ~-thromboglobulin concentrations that PDGF in those cysts was most probably not derived from haematopoetic cells. PDGF has been implicated in the control of glioma proliferation and invasion in an autocrine loop fashion [34].…”
Section: Discussionmentioning
confidence: 97%
“…The mechanisms of cyst formation suggest that cyst fluids may accumulate a variety of tumour cell produced soluble factors or factors released by normal reactive brain cells within tumour tissue or within the cyst walls. In fact, tumour cell growth promoting activity has been identified in glioma cyst fluids in experimental model systems [28,37] and subsequently different authors have demonstrated several growth factors such as PDGF, aFGF, VEGF, as well as somatomedins contained in cyst fluids of gliomas [24,25,29,35].…”
Section: Introductionmentioning
confidence: 98%